2015
DOI: 10.3171/2014.10.jns13395
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effectiveness of antibiotic-impregnated shunt catheters in the treatment of adult and pediatric hydrocephalus: analysis of 12,589 consecutive cases from 287 US hospital systems

Abstract: OBJECT The real-world effectiveness of antibiotic-impregnated shunt catheters to reduce the incidence of shunt infections is still debated. The literature to date consists mostly of small, single-institution studies. The aim of this study was to assess the incidence of infection for antibiotic-impregnated catheters (AICs) versus standard shunt catheters in a large nationwide administrative database. METHODS The authors retrospectively reviewed hospital discharge and billing records from the Premier Perspectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 47 publications
(34 reference statements)
0
24
0
3
Order By: Relevance
“…Use of antimicrobial-impregnated shunts has not only reduced the incidence of CSF shunt infections but also has resulted in significant hospital cost savings [181]. In a study that compared the effectiveness of antimicrobial-impregnated shunt catheters in treatment of 12 589 consecutive cases from 287 hospital systems in adult and pediatric patients with hydrocephalus [182], antimicrobial-impregnated catheter use was associated with a significant reduction in infection in both adult (2.2% vs 3.6%; P = .02) and pediatric (2.6% vs 7.1%; P < .01) patients. Reduced infection was demonstrated regardless of hospital size, annual shunt volume, hospital location, or patient risk factors.…”
Section: Antimicrobial-impregnated Cathetersmentioning
confidence: 99%
“…Use of antimicrobial-impregnated shunts has not only reduced the incidence of CSF shunt infections but also has resulted in significant hospital cost savings [181]. In a study that compared the effectiveness of antimicrobial-impregnated shunt catheters in treatment of 12 589 consecutive cases from 287 hospital systems in adult and pediatric patients with hydrocephalus [182], antimicrobial-impregnated catheter use was associated with a significant reduction in infection in both adult (2.2% vs 3.6%; P = .02) and pediatric (2.6% vs 7.1%; P < .01) patients. Reduced infection was demonstrated regardless of hospital size, annual shunt volume, hospital location, or patient risk factors.…”
Section: Antimicrobial-impregnated Cathetersmentioning
confidence: 99%
“…Cost analysis studies have demonstrated that use of the more expensive impregnated catheters is supported. 51,55 The most recent guidelines from the Infectious Diseases Society of America's Clinical Practice Guidelines for Healthcare-Associated Ventriculitis and Meningitis recommend placement of antibiotic-impregnated shunts. 28 However, the largest international, prospective, randomized trial of 434 patients failed to find a significant benefit to the use of antibiotic-impregnated catheters, with a 2.3% infection rate for impregnated catheters compared with a 2.8% infection rate for standard catheters.…”
Section: Prophylaxismentioning
confidence: 99%
“…Las revisiones sistemáticas disponibles favorecen su utilización, sin diferenciar entre los recubiertos por clindamicina o minociclina con rifampicina, al encontrar reducción neta estadísticamente significativa del riesgo de infección. Lo anterior es aplicable a todos los grupos de edad evaluados (neonatos, población pediátrica y adulta) con una reducción más evidente en la infección causada por Staphylococcus spp (25)(26)(27)(28)(29)(30)(31)(32)(33) . No obstante, también existen estudios que no encuentran diferencia en la ocurrencia de infección con el uso de estos dispositivos y no recomiendan su uso (34,35) , aunque la IDSA los recomienda (7) .…”
Section: Catéteres Impregnados Con Antibióticos O Iones De Plataunclassified